Research on the impact of live streaming marketing by online influencers on consumer purchasing intentions - Wang, Xueli; Aisihaer, Nadilai; Aihemaiti, Aihetanmujiang (Frontiers in Psychology, 2022)
Drawing from the stimulus–organism–response (S-O-R) model, this study explores the impact on consumer attitudes in the context of Chinese online influencers' e-commerce live streaming. To examine this impact, we distributed our survey questionnaire to Chinese consumers with live streaming shopping experiences. Using data from 430 valid questionnaires, a hierarchical regression analysis was used to examine our hypotheses. The results show that expertise, bargaining power, post-sales services, and live streaming schedules of online influencers affect consumer trust in online influencers. The expertise, bargaining power, and livestreaming schedules of online influencers affect consumer impulsivity. Moreover, the trust and impulsiveness of online influencers increase consumer purchasing intentions. The implications and future research directions are discussed in this article.